the Pengembangan Sistem E-Learning berbasis Website di SD Negeri 3 Sesetan : - - I Made Dedy Setiawan (UNIB Press, 2024)
Schools as one part of the educational unit have a fairly central role in facilitating learning activities through the use of technology. One use of technology in learning that is relevant in the current digital era is the use of e-learning. This research aims to develop a web-based e-learning system at SD Negeri 3 Sesetan. This research includes development research using the waterfall model which consists of the stages of needs analysis, system design, implementation, program testing and maintenance. Research subjects are participants involved as users and implementers in the field of e-learning. Data collection methods use questionnaires, observation methods, literature studies, and documentation. Next, the data was analyzed quantitatively, comparative analysis, deepening and sharpening were carried out in the form of limited discussions. The web-based e-learning system developed at SD Negeri 3 Sesetan provides a percentage of scores with good qualifications. Apart from that, the web-based e-learning design is in accordance with the curriculum and needs of teachers and students. Based on the results of this research, it can be concluded that web-based e-learning products are suitable for use as support for learning activities at SD Negeri 3 Sesetan.